Mini Hyrax vs Hyrax expanders in the rapid palatal expansion in adolescents with posterior crossbite: a randomized controlled clinical trial - Giordani Santos Silveira; Lucas Guimarães Abreu; Juan Martin Palomo; Larissa Salgado da Matta Cid Pinto; Adriana Alkmim de Sousa; Bruno Frazão Gribel; Dauro Douglas Oliveira (SpringerOpen, 2021)
Abstract Purpose The aim of this study was to compare the dental effects, impact on quality of life, and pain perception of adolescents wearing Mini Hyrax and Hyrax expanders in rapid palatal expansion. Methods Thirty-four adolescents aged 11 to 16 years, with maxillary transverse deficiency (unilateral or bilateral posterior crossbite), were randomly allocated into two groups, Mini Hyrax group and Hyrax group (1:1 ratio). Dental effects were evaluated by digitally superimposed pretreatment and postretention three-dimensional intraoral scans on the palatal rugaes using the software 3DSlicer. Impact on quality of life was assessed with the OHIP-14 questionnaire applied in the pretreatment, posttreatment and postretention. Visual analog scale was applied 24, 48, and 72 h and 7 days after the first activation of the expander. Results Thirty of the 34 adolescents recruited completed the study. There were no statistically significant differences in dentoalveolar effects between groups. OHIP-14 scores across time among Mini Hyrax wearers were similar to those of the Hyrax wearers. The inter-group comparisons showed no difference between groups with respect to the OHIP-14 scores in posttreatment and postretention (p > 0.05). There were no differences in pain perception between groups. Considering intra-group comparison, the reduction in pain perception among adolescents in the Mini Hyrax group was gradual. Among adolescents in the Hyrax group, a statistically significant reduction between 48 and 72 h was observed. Conclusion There were no significant differences in dental effects, impact on quality of life and pain perception between adolescents wearing Mini Hyrax and Hyrax expanders in rapid palatal expansion.